Positive electrode and lithium secondary battery comprising the same
Patent Information
- Application Number
- CN202280012254.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-02-26
- Filing Date
- 2022-02-25
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-02-25
AI Technical Summary
因此,存在电极快速劣化而降低寿命特性的问题
[0012]由于本发明的正极包括两个正极活性材料层,并且通过在与电解液接触的上部正极活性材料层上设置镍/钴摩尔比相对较小的正极活性材料来改善正极活性材料层中的锂迁移率,因此可以改善寿命特性。
Smart Images

Figure BDA0004363934610000151
Abstract
Description
Technical Field
[0001] This application claims priority to Korean Patent Application No. 10-2021-0026597, filed on February 26, 2021, the disclosure of which is incorporated herein by reference.
[0002] The present invention relates to a positive electrode and a lithium secondary battery comprising the same, and more particularly, to a high-load positive electrode having improved life characteristics and a lithium secondary battery comprising the same. Background Technology
[0003] With the increasing demand for mobile devices and electric vehicles, the demand for secondary batteries as an energy source has increased significantly. Among these secondary batteries, lithium secondary batteries with high energy density and low self-discharge rate have been commercialized and are widely used.
[0004] Recently, the demand for high-capacity batteries in industrial sectors such as electric vehicles and energy storage systems (ESS) is increasing, and therefore a high-load cathode is being developed, which includes a high-nickel (high-Ni) cathode active material that has excellent capacity characteristics under high load.
[0005] High-load cathodes offer the advantage of excellent capacity characteristics. However, as the loading increases, lithium (Li) becomes less mobile within the cathode active material layer, resulting in a relatively large number of lithium ions migrating to the surface compared to the active material layer itself. This leads to rapid electrode degradation and reduced lifetime characteristics. Therefore, there is a need to develop a high-load electrode with superior lifetime characteristics. Summary of the Invention
[0006] Technical issues
[0007] One aspect of the present invention provides a high-load positive electrode and a lithium secondary battery comprising the positive electrode, wherein the lithium mobility in the positive electrode active material layer is improved by controlling the nickel / cobalt molar ratio of the positive electrode active material disposed on the surface and inside the positive electrode active material layer, thereby improving lifetime characteristics.
[0008] Technical solution
[0009] According to one aspect of the present invention, a positive electrode is provided, comprising a positive electrode current collector, a first positive electrode active material layer formed on the positive electrode current collector and comprising a first positive electrode active material, and a second positive electrode active material layer formed on the first positive electrode active material layer and comprising a second positive electrode active material, wherein the first positive electrode active material and the second positive electrode active material comprise lithium nickel cobalt oxide, wherein the nickel content in all metal components other than lithium is 80 atm% or more, the nickel / cobalt molar ratio of the first positive electrode active material is 18 or more, and the nickel / cobalt molar ratio of the second positive electrode active material is less than 18.
[0010] According to another aspect of the present invention, a lithium secondary battery is provided, which includes the above-described positive electrode.
[0011] Beneficial effects
[0012] Since the cathode of the present invention comprises two cathode active material layers, and the lithium mobility in the cathode active material layer is improved by providing a cathode active material with a relatively small nickel / cobalt molar ratio on the upper cathode active material layer in contact with the electrolyte, the lifetime characteristics can be improved. Detailed Implementation
[0013] The present invention will be described in detail below.
[0014] As a result of extensive research into improving the lifetime characteristics of lithium secondary batteries using high-load cathodes, the inventors discovered that by forming a cathode active material layer with a bilayer structure that satisfies a specific nickel / cobalt molar ratio, the lifetime characteristics of high-load electrodes can be improved, thus completing this invention.
[0015] positive electrode
[0016] The positive electrode of the present invention includes a positive current collector, a first positive active material layer formed on the positive current collector and containing a first positive active material, and a second positive active material layer formed on the first positive active material layer and containing a second positive active material.
[0017] The positive current collector is used to support the positive active material layer, and can be any positive current collector commonly used in the art. For example, the positive current collector can be a film, sheet, foil, mesh, porous body, foam, or nonwoven fabric formed of materials such as aluminum, stainless steel, nickel, or titanium.
[0018] Furthermore, the surface of the positive electrode current collector can be treated to improve physical properties such as adhesion and strength. For example, the positive electrode current collector may include a coating made of materials such as carbon, nickel, titanium and silver on its surface, or micro-irregularities may be formed on its surface.
[0019] The thickness of the positive current collector is typically 3 μm to 500 μm.
[0020] The first positive electrode active material layer is a positive electrode active material layer formed on the positive electrode current collector, namely the lower positive electrode active material layer, wherein the lower positive electrode active material layer includes the first positive electrode active material.
[0021] The first positive electrode active material is a lithium transition metal oxide containing nickel and cobalt, specifically, a lithium-nickel-cobalt-based oxide, wherein the content of nickel in the metal components excluding lithium is 80 mol% or more, preferably 90 mol% or more, more preferably 90 mol% to 95 mol%, and the nickel / cobalt molar ratio is 18 or more, for example 18 to 50. When the amount of nickel in the first positive electrode active material satisfies the above range, high capacity characteristics can be achieved. Furthermore, when the nickel / cobalt molar ratio of the first positive electrode active material is outside the above range, the effect of improving the mobility of lithium in the positive electrode active material layer is not significant.
[0022] Preferably, the first positive electrode active material may be a lithium transition metal oxide represented by the following [Formula 1].
[0023] [Formula 1]
[0024] Li a1 [Ni x1 Co y1 M 1 z1 M 2 w1 O2
[0025] In Formula 1, M 1 may be manganese (Mn), aluminum (Al) or a combination thereof, preferably may be Mn or a combination of Mn and Al.
[0026] M 2 may be at least one selected from the group consisting of zirconium (Zr), boron (B), tungsten (W), magnesium (Mg), cerium (Ce), hafnium (Hf), tantalum (Ta), lanthanum (La), titanium (Ti), strontium (Sr), barium (Ba), fluorine (F), phosphorus (P) and sulfur (S).
[0027] a1 represents the molar ratio of lithium in the lithium transition metal oxide, wherein a1 may satisfy 0.8≤a1≤1.2, 0.9≤a1≤1.1, or 0.95≤a1≤1.1.
[0028] x1 represents the molar ratio of nickel in the metal components excluding lithium in the lithium transition metal oxide, wherein x1 may satisfy 0.90≤x1<1, 0.90≤x1≤0.98, or 0.90≤x1≤0.95. When the molar ratio of nickel satisfies the above range, excellent capacity characteristics can be achieved.
[0029] y1 represents the molar ratio of cobalt in the metal components excluding lithium in the lithium transition metal oxide, wherein y1 may satisfy 0<y1<0.10, 0.01≤y1<0.10, or 0.01≤y1≤0.06.
[0030] z1 represents the molar ratio of M in the metal components excluding lithium in the lithium transition metal oxide1 wherein z1 may satisfy 0<z1<0.10, 0.01≤z1≤0.08, or 0.01≤z1≤0.06, representing the molar ratio of
[0031] w1 represents M in the metal components other than lithium in the lithium transition metal oxide 2 wherein w1 may satisfy 0≤w1<0.10, 0≤w1≤0.05, or 0≤w1≤0.02, representing the molar ratio of
[0032] In Formula 1, the nickel / cobalt molar ratio (i.e., x1 / y1) may be 18 or more, for example, 18 to 50. In the case where x1 / y1 is less than 18, the effect of improving lithium mobility in the high-loading positive electrode active material layer is not significant.
[0033] For example, the first positive electrode active material may have a cation mixing degree of greater than 1.2%, preferably greater than 1.2% and less than or equal to 2.0%.
[0034] Based on the total weight of the first positive electrode active material layer, the content of the first positive electrode active material may be 80 wt% or more, preferably 80 wt% to 100 wt%, and more preferably 85 wt% to 98 wt%. When the amount of the first positive electrode active material satisfies the above range, lithium ions can move more smoothly in the high-loading electrode during charging and discharging.
[0035] In addition, the thickness of the first positive electrode active material layer may be 30 μm to 300 μm, preferably 50 μm to 200 μm, and more preferably 70 μm to 150 μm. When the thickness of the first positive electrode active material layer satisfies the above range, high-loading characteristics can be achieved.
[0036] Then, the second positive electrode active material layer is a positive electrode active material layer formed on the first positive electrode active material layer, that is, an upper positive electrode active material layer, wherein the upper positive electrode active material layer contains the second positive electrode active material.
[0037] The second positive electrode active material is a lithium transition metal oxide containing nickel and cobalt, specifically a lithium nickel-cobalt-based oxide, wherein the content of nickel in the metal components other than lithium is 80 mol% or more, preferably 80 mol% or more and less than 90 mol%, more preferably 81 mol% to 89 mol%, and the nickel / cobalt molar ratio is less than 18, preferably 5 to 17.8, and more preferably 7 to 17.6.
[0038] When the nickel content of the second positive electrode active material satisfies the above range, high-capacity characteristics can be achieved. Furthermore, in the case where the nickel / cobalt molar ratio of the second positive electrode active material satisfies the above range, since the movement of lithium ions on the surface and inside of the positive electrode active material layer is balanced, rapid structural deterioration occurring on the surface of the positive electrode active material layer can be prevented.
[0039] Preferably, the second positive electrode active material may be a lithium transition metal oxide represented by the following [Formula 2].
[0040] [Formula 2]
[0041] Li a2 [Ni x2 Co y2 M 3 z2 M 4 w2 O2
[0042] In Formula 2,
[0043] M 3 may be Mn, Al, or a combination thereof, and preferably may be Mn or a combination of Mn and Al.
[0044] M 4 may be at least one selected from the group consisting of Zr, B, W, Mg, Ce, Hf, Ta, La, Ti, Sr, Ba, F, P, and S.
[0045] a2 represents the molar ratio of lithium in the lithium transition metal oxide, wherein a2 may satisfy 0.8≤a2≤1.2, 0.9≤a2≤1.1, or 0.95≤a2≤1.1.
[0046] x2 represents the molar ratio of nickel in the metal components other than lithium in the lithium transition metal oxide, wherein x2 may satisfy 0.80≤x2<0.90, 0.81≤x2≤0.89, or 0.83≤x2≤0.89. When the molar ratio of nickel satisfies the above range, excellent capacity characteristics can be obtained.
[0047] y2 represents the molar ratio of cobalt in the metal components other than lithium in the lithium transition metal oxide, wherein y2 may satisfy 0<y2<0.20, 0.01≤y2<0.20, or 0.01≤y2≤0.15.
[0048] z2 represents the molar ratio of M in the metal components other than lithium in the lithium transition metal oxide 3 , wherein z2 may satisfy 0<z2<0.20, 0.01≤z2<0.20, or 0.01≤z2≤0.15.
[0049] w2 represents the molar ratio of M in the metal components other than lithium in the lithium transition metal oxide 4 , wherein w2 may satisfy 0≤w2<0.20, 0≤w2≤0.10, or 0≤w2≤0.05.
[0050] In Equation 2, the nickel / cobalt molar ratio, i.e., x2 / y2, can be less than 18, preferably 5 to 17.8, and more preferably 7 to 17.6. When x2 / y2 is 18 or higher, the effect on improving lithium mobility in the highly loaded cathode active material layer is not significant.
[0051] Ideally, the cation mixing degree of the second positive electrode active material should be 1.2% or less, for example, 1.0% or less. When the cation mixing degree of the second positive electrode active material meets the above range, that is, when the cation mixing degree of the second positive electrode active material is lower than that of the first positive electrode active material, the effect of further improving lithium mobility can be obtained.
[0052] Based on the total weight of the second positive electrode active material layer, the content of the second positive electrode active material can be 80% by weight or more, preferably 80% by weight to 100% by weight, and more preferably 85% by weight to 98% by weight. When the amount of the second positive electrode active material meets the above range, lithium ions can move smoothly in the high-load electrode during charging and discharging.
[0053] Furthermore, the thickness of the second positive electrode active material layer can be less than 10 μm, preferably 1 μm to 10 μm, and more preferably 2 μm to 5 μm. When the thickness of the second positive electrode active material layer meets the above range, lifetime degradation caused by lithium mobility imbalance can be effectively suppressed, while minimizing the reduction in energy density.
[0054] In addition to containing positive electrode active materials, the first positive electrode active material layer and the second positive electrode active material layer may also contain conductive agents and binders.
[0055] Conductive agents are used to provide conductivity to electrodes. Any conductive agent can be used without particular limitation, as long as it has suitable electronic conductivity without causing adverse chemical changes in the battery. Specific examples of conductive agents can be: graphite, such as natural or artificial graphite; carbon-based materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermally cracked carbon black, and carbon fibers; metal powders or fibers, such as copper, nickel, aluminum, and silver; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, or any one or a mixture of two or more of these.
[0056] Based on the total weight of the first positive electrode active material layer or the second positive electrode active material layer, the content of the conductive agent can be less than 10% by weight, preferably from 0.2% to 5% by weight, and more preferably from 0.5% to 2% by weight. When the amount of conductive agent meets the above range, the electrochemical performance and energy density can be optimized.
[0057] Adhesives are used to improve the adhesion between positive electrode active material particles and the adhesion between the positive electrode active material and the current collector, wherein adhesives known in the art can be used.
[0058] For example, as an adhesive, polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof can be used, and any one or a mixture of two or more thereof can be used.
[0059] Based on the total weight of the first or second positive electrode active material layer, the binder content can be less than 10% by weight, preferably from 0.2% to 5% by weight, and more preferably from 0.5% to 2% by weight. When the binder content meets the above range, the electrochemical performance and energy density can be optimized.
[0060] The positive electrode loading is 4 mAh / cm². 2 For example, 4mAh / cm 2 Up to 20mAh / cm 2 High energy density can be achieved when the load meets the above range.
[0061] After preparing a first positive electrode slurry composition containing a first positive electrode active material and a second active material slurry composition containing a second positive electrode, the positive electrode of the present invention can be prepared by sequentially coating the first positive electrode slurry composition and the second positive electrode slurry composition.
[0062] For example, after coating a first positive electrode slurry composition onto a positive electrode current collector and drying it to form a first positive electrode active material layer, and coating a second positive electrode slurry composition onto the first positive electrode active material layer and drying it to form a second positive electrode active material layer, the positive electrode of the present invention can be prepared by roll pressing.
[0063] Furthermore, after coating the first positive electrode slurry composition onto a separate carrier and drying it to form a first positive electrode active material layer, and coating the second positive electrode slurry composition onto the first positive electrode active material layer and drying it to form a second positive electrode active material layer, the positive electrode of the present invention can be prepared by separating the stacked layer of the first positive electrode active material layer and the second positive electrode active material layer from the carrier and stacking the stacked layer onto the positive electrode current collector.
[0064] The first and second positive electrode slurry compositions can be prepared by dispersing the positive electrode active material, conductive agent, and binder in a solvent. In this case, solvents commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), acetone, water, or mixtures thereof, can be used. In this case, considering the coating thickness and production yield of the positive electrode slurry, the amount of solvent used allows the solvent to dissolve or disperse the positive electrode active material, conductive agent, and binder, and allows it to have a viscosity that provides excellent thickness uniformity during coating.
[0065] Lithium secondary batteries
[0066] Next, the lithium secondary battery of the present invention will be described.
[0067] The lithium secondary battery of the present invention includes the positive electrode of the present invention as described above. Specifically, the lithium secondary battery of the present invention may include the positive electrode of the present invention, a negative electrode disposed facing the positive electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte. Since the positive electrode is the same as described above, its detailed description will be omitted, and only the remaining configurations will be described in detail below.
[0068] The negative electrode includes a negative electrode current collector and a layer of negative electrode active material disposed on the negative electrode current collector.
[0069] There are no particular limitations on the negative electrode current collector, as long as it has high conductivity and will not cause adverse chemical changes in the battery. Materials used include, for example, copper, stainless steel, aluminum, nickel, titanium, sintered carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., and aluminum-cadmium alloys. Furthermore, the thickness of the negative electrode current collector can typically range from 3 μm to 500 μm, and similar to the positive electrode current collector, microscopic irregularities can be formed on the surface of the current collector to improve the adhesion of the negative electrode active material. For example, the negative electrode current collector can be used in various shapes, such as films, sheets, foils, meshes, porous bodies, foams, nonwoven fabrics, etc.
[0070] In addition to the negative electrode active material, the negative electrode active material layer may optionally include a binder and a conductive agent.
[0071] Compounds capable of reversibly inserting and de-intercalating lithium can be used as anode active materials. Specific examples of anode active materials can be carbonaceous materials, such as artificial graphite, natural graphite, graphitized carbon fibers, and amorphous carbon; metallic materials that can be alloyed with lithium, such as silicon (Si), aluminum (Al), tin (Sn), lead (Pb), zinc (Zn), bismuth (Bi), indium (In), magnesium (Mg), gallium (Ga), cadmium (Cd), Si alloys, Sn alloys, or Al alloys; and metal oxides that can be doped and de-doped with lithium, such as SiO2. β(0<β<2), SnO2, vanadium oxide, and lithium vanadium oxide; or composites of metallic and carbonaceous materials, such as Si-C composites or Sn-C composites, and any one or a mixture of more than two of these can be used. Furthermore, lithium metal films can be used as anode active materials. Additionally, both low-crystallinity carbon and high-crystallinity carbon can be used as carbon materials. Typical examples of low-crystallinity carbon can be soft carbon and hard carbon, while typical examples of high-crystallinity carbon can be irregular, planar, sheet-like, spherical, or fibrous natural or artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch-based carbon fibers, mesophase carbon microspheres, mesophase pitch, and high-temperature sintered carbon, such as coke derived from petroleum or coal tar pitch.
[0072] Based on the total weight of the negative electrode active material layer, the content of the negative electrode active material can be from 80% to 99% by weight.
[0073] The binder is a component that facilitates the bonding between the conductive agent, the active material, and the current collector, wherein the amount of binder added is typically from 0.1% to 10% by weight, based on the total weight of the negative electrode active material layer. Examples of binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile rubber, fluororubber, and various copolymers thereof.
[0074] A conductive agent is a component used to further improve the conductivity of the negative electrode active material, wherein the amount of conductive agent added can be less than 10% by weight, for example, less than 5% by weight, based on the total weight of the negative electrode active material layer. There are no particular limitations on the conductive agent, as long as it is conductive and does not cause adverse chemical changes in the battery. For example, conductive materials such as: graphite, such as natural or artificial graphite; carbon black, such as acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermally cracked carbon black; conductive fibers, such as carbon fibers or metal fibers; metal powders, such as fluorocarbon powder, aluminum powder, and nickel powder; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or polyphenylene derivatives.
[0075] The negative electrode active material layer can be prepared by coating a negative electrode slurry composition onto a negative electrode current collector and drying the coated negative electrode current collector, or by casting a negative electrode slurry composition onto a separate carrier and then stacking a film layer separated from the carrier onto the negative electrode current collector. The negative electrode slurry composition is prepared by dissolving or dispersing the negative electrode active material, along with optional binders and conductive agents, in a solvent.
[0076] In lithium-ion secondary batteries, the separator separates the negative and positive electrodes and provides a path for lithium ions to move. Any separator can be used without particular limitation, as long as it is generally suitable for lithium-ion secondary batteries. Specifically, separators with high electrolyte retention capacity and low resistance to electrolyte ion transfer can be used. Porous polymer membranes can be used, such as porous polymer membranes prepared from polyolefin polymers, such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers, and ethylene / methacrylate copolymers, or laminated structures of two or more layers. Alternatively, conventional porous nonwoven fabrics can be used, such as nonwoven fabrics formed from high-melting-point glass fibers or polyethylene terephthalate fibers. Furthermore, coated separators including ceramic components or polymer materials can be used to ensure heat resistance or mechanical strength, and single-layer or multi-layer separator structures can be optionally used.
[0077] Furthermore, the electrolyte used in this invention may include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, or molten inorganic electrolytes that can be used to prepare lithium secondary batteries, but this invention is not limited thereto.
[0078] Specifically, electrolytes may include organic solvents and lithium salts.
[0079] Any organic solvent can be used without particular limitation, as long as it can serve as a medium through which ions participating in the electrochemical reactions of the battery move. Specifically, as organic solvents, ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone, and ε-lactamolactone can be used; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; or carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), and propylene carbonate (PC); alcohol solvents such as ethanol and isopropanol; nitriles such as R-CN (where R is a straight-chain, branched, or cyclic C2-C20 hydrocarbon group, and may include double-bonded aromatic rings or ether bonds); amides such as dimethylformamide; dioxolane, such as 1,3-dioxolane; or sulfolane.
[0080] Lithium salts can be used without particular restrictions, as long as they are compounds that can provide lithium ions for lithium secondary batteries. Specifically, LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2 can be used. Lithium salts can be used in concentrations ranging from 0.1M to 2.0M. If the concentration of the lithium salt is within this range, excellent electrolyte performance can be obtained because the electrolyte can have suitable conductivity and viscosity, and lithium ions can move efficiently.
[0081] The invention will now be described in more detail by way of specific embodiments. However, the invention may be embodied in many different forms and should not be construed as limited to the embodiments set forth herein. Rather, these embodiments are provided to make the disclosure thorough and complete and to fully convey the scope of the invention to those skilled in the art.
[0082] Example 1
[0083] LiNi with a cation mixing degree of 1.3% was used as the first positive electrode active material. 0.9 Co 0.05 Mn 0.05 O2, carbon black as a conductive agent, and polyvinylidene fluoride as a binder are mixed in N-methylpyrrolidone solvent to make the weight ratio of positive electrode active material: conductive agent: binder 98.5:0.5:1, so as to prepare the first positive electrode slurry.
[0084] LiNi, with a cation mixing degree of less than 1%, will be used as the second positive electrode active material. 0.83 Co 0.11 Mn 0.06 O2, carbon black as a conductive agent, and polyvinylidene fluoride as a binder are mixed in N-methylpyrrolidone solvent to make the weight ratio of positive electrode active material: conductive agent: binder 98.5:0.5:1, so as to prepare a second positive electrode slurry.
[0085] After coating a first positive electrode slurry composition onto an aluminum current collector and drying it to form a first positive electrode active material layer, a second positive electrode slurry composition is coated onto the first positive electrode active material layer, dried at 130°C, and then rolled to prepare the positive electrode. In this case, based on the cross-section of the positive electrode, the thickness of the first positive electrode active material layer is 98 μm, the thickness of the second positive electrode active material layer is 2 μm, and the positive electrode loading is 6.85 mAh / cm². 2 .
[0086] Example 2
[0087] LiNi with a cation mixing degree of 1.5% was used as the first positive electrode active material. 0.9 Co 0.04 Mn 0.06 O2, carbon black as a conductive agent, and polyvinylidene fluoride as a binder are mixed in N-methylpyrrolidone solvent to make the weight ratio of positive electrode active material: conductive agent: binder 98.5:0.5:1, so as to prepare the first positive electrode slurry.
[0088] LiNi, with a cation mixing degree of less than 1%, will be used as the second positive electrode active material. 0.85 Co 0.07 Mn 0.08 O2, carbon black as a conductive agent, and polyvinylidene fluoride as a binder are mixed in N-methylpyrrolidone solvent to make the weight ratio of positive electrode active material: conductive agent: binder 98.5:0.5:1, so as to prepare a second positive electrode slurry.
[0089] After coating a first positive electrode slurry composition onto an aluminum current collector and drying it to form a first positive electrode active material layer, a second positive electrode slurry composition is coated onto the first positive electrode active material layer, dried at 130°C, and then rolled to prepare the positive electrode. In this case, based on the cross-section of the positive electrode, the thickness of the first positive electrode active material layer is 98 μm, the thickness of the second positive electrode active material layer is 2 μm, and the positive electrode loading is 6.85 mAh / cm². 2 .
[0090] Example 3
[0091] LiNi with a cation mixing degree of 1.7% was used as the first positive electrode active material. 0.9 Co 0.02 Mn 0.08 O2, carbon black as a conductive agent, and polyvinylidene fluoride as a binder are mixed in N-methylpyrrolidone solvent to make the weight ratio of positive electrode active material: conductive agent: binder 98.5:0.5:1, so as to prepare the first positive electrode slurry.
[0092] LiNi with a cation mixing degree of 1.2% was used as the second positive electrode active material. 0.88 Co 0.05 Mn 0.07 O2, carbon black as a conductive agent, and polyvinylidene fluoride as a binder are mixed in N-methylpyrrolidone solvent to make the weight ratio of positive electrode active material: conductive agent: binder 98.5:0.5:1, so as to prepare a second positive electrode slurry.
[0093] After coating a first positive electrode slurry composition onto an aluminum current collector and drying it to form a first positive electrode active material layer, a second positive electrode slurry composition is coated onto the first positive electrode active material layer, dried at 130°C, and then rolled to prepare the positive electrode. In this case, based on the cross-section of the positive electrode, the thickness of the first positive electrode active material layer is 98 μm, the thickness of the second positive electrode active material layer is 2 μm, and the positive electrode loading is 6.9 mAh / cm³. 2 .
[0094] Example 4
[0095] LiNi with a cation mixing degree of 1.3% was used as the first positive electrode active material. 0.92 Co 0.05 Mn 0.03 O2, carbon black as a conductive agent, and polyvinylidene fluoride as a binder are mixed in N-methylpyrrolidone solvent to make the weight ratio of positive electrode active material: conductive agent: binder 98.5:0.5:1, so as to prepare the first positive electrode slurry.
[0096] LiNi, with a cation mixing degree of less than 1%, will be used as the second positive electrode active material. 0.83 Co 0.11 Mn 0.06 O2, carbon black as a conductive agent, and polyvinylidene fluoride as a binder are mixed in N-methylpyrrolidone solvent to make the weight ratio of positive electrode active material: conductive agent: binder 98.5:0.5:1, so as to prepare a second positive electrode slurry.
[0097] After coating a first positive electrode slurry composition onto an aluminum current collector and drying it to form a first positive electrode active material layer, a second positive electrode slurry composition is coated onto the first positive electrode active material layer, dried at 130°C, and then rolled to prepare the positive electrode. In this case, based on the cross-section of the positive electrode, the thickness of the first positive electrode active material layer is 98 μm, the thickness of the second positive electrode active material layer is 2 μm, and the positive electrode loading is 6.9 mAh / cm³. 2 .
[0098] Example 5
[0099] LiNi with a cation mixing degree of 1.4% was used as the first positive electrode active material. 0.92 Co 0.04 Mn 0.04 O2, carbon black as a conductive agent, and polyvinylidene fluoride as a binder are mixed in N-methylpyrrolidone solvent to make the weight ratio of positive electrode active material: conductive agent: binder 98.5:0.5:1, so as to prepare the first positive electrode slurry.
[0100] LiNi, with a cation mixing degree of less than 1%, will be used as the second positive electrode active material.0.85 Co 0.07 Mn 0.08 O2, carbon black as a conductive agent, and polyvinylidene fluoride as a binder are mixed in N-methylpyrrolidone solvent to make the weight ratio of positive electrode active material: conductive agent: binder 98.5:0.5:1, so as to prepare a second positive electrode slurry.
[0101] After coating a first positive electrode slurry composition onto an aluminum current collector and drying it to form a first positive electrode active material layer, a second positive electrode slurry composition is coated onto the first positive electrode active material layer, dried at 130°C, and then rolled to prepare the positive electrode. In this case, based on the cross-section of the positive electrode, the thickness of the first positive electrode active material layer is 98 μm, the thickness of the second positive electrode active material layer is 2 μm, and the positive electrode loading is 6.9 mAh / cm³. 2 .
[0102] Example 6
[0103] LiNi with a cation mixing degree of 1.7% was used as the first positive electrode active material. 0.92 Co 0.02 Mn 0.06 O2, carbon black as a conductive agent, and polyvinylidene fluoride as a binder are mixed in N-methylpyrrolidone solvent to make the weight ratio of positive electrode active material: conductive agent: binder 98.5:0.5:1, so as to prepare the first positive electrode slurry.
[0104] LiNi with a cation mixing degree of 1.2% was used as the second positive electrode active material. 0.88 Co 0.05 Mn 0.07 O2, carbon black as a conductive agent, and polyvinylidene fluoride as a binder are mixed in N-methylpyrrolidone solvent to make the weight ratio of positive electrode active material: conductive agent: binder 98.5:0.5:1, so as to prepare a second positive electrode slurry.
[0105] After coating a first positive electrode slurry composition onto an aluminum current collector and drying it to form a first positive electrode active material layer, a second positive electrode slurry composition is coated onto the first positive electrode active material layer, dried at 130°C, and then rolled to prepare the positive electrode. In this case, based on the cross-section of the positive electrode, the thickness of the first positive electrode active material layer is 98 μm, the thickness of the second positive electrode active material layer is 2 μm, and the positive electrode loading is 6.9 mAh / cm³. 2 .
[0106] Example 7
[0107] LiNi with a cation mixing degree of 1.4% was used as the first positive electrode active material. 0.94 Co 0.05 Mn0.01 O2, carbon black as a conductive agent, and polyvinylidene fluoride as a binder are mixed in N-methylpyrrolidone solvent to make the weight ratio of positive electrode active material: conductive agent: binder 98.5:0.5:1, so as to prepare the first positive electrode slurry.
[0108] LiNi, with a cation mixing degree of less than 1%, will be used as the second positive electrode active material. 0.83 Co 0.11 Mn 0.06 O2, carbon black as a conductive agent, and polyvinylidene fluoride as a binder are mixed in N-methylpyrrolidone solvent to make the weight ratio of positive electrode active material: conductive agent: binder 98.5:0.5:1, so as to prepare a second positive electrode slurry.
[0109] After coating a first positive electrode slurry composition onto an aluminum current collector and drying it to form a first positive electrode active material layer, a second positive electrode slurry composition is coated onto the first positive electrode active material layer, dried at 130°C, and then rolled to prepare the positive electrode. In this case, based on the cross-section of the positive electrode, the thickness of the first positive electrode active material layer is 98 μm, the thickness of the second positive electrode active material layer is 2 μm, and the positive electrode loading is 6.9 mAh / cm³. 2 .
[0110] Example 8
[0111] LiNi with a cation mixing degree of 1.5% was used as the first positive electrode active material. 0.94 Co 0.04 Mn 0.02 O2, carbon black as a conductive agent, and polyvinylidene fluoride as a binder are mixed in N-methylpyrrolidone solvent to make the weight ratio of positive electrode active material: conductive agent: binder 98.5:0.5:1, so as to prepare the first positive electrode slurry.
[0112] LiNi, with a cation mixing degree of less than 1%, will be used as the second positive electrode active material. 0.85 Co 0.07 Mn 0.06 O2, carbon black as a conductive agent, and polyvinylidene fluoride as a binder are mixed in N-methylpyrrolidone solvent to make the weight ratio of positive electrode active material: conductive agent: binder 98.5:0.5:1, so as to prepare a second positive electrode slurry.
[0113] After coating a first positive electrode slurry composition onto an aluminum current collector and drying it to form a first positive electrode active material layer, a second positive electrode slurry composition is coated onto the first positive electrode active material layer, dried at 130°C, and then rolled to prepare the positive electrode. In this case, based on the cross-section of the positive electrode, the thickness of the first positive electrode active material layer is 98 μm, the thickness of the second positive electrode active material layer is 2 μm, and the positive electrode loading is 7 mAh / cm³. 2 .
[0114] Example 9
[0115] LiNi with a cation mixing degree of 1.7% was used as the first positive electrode active material. 0.94 Co 0.02 Mn 0.04 O2, carbon black as a conductive agent, and polyvinylidene fluoride as a binder are mixed in N-methylpyrrolidone solvent to make the weight ratio of positive electrode active material: conductive agent: binder 98.5:0.5:1, so as to prepare the first positive electrode slurry.
[0116] LiNi with a cation mixing degree of 1.2% was used as the second positive electrode active material. 0.88 Co 0.05 Mn 0.07 O2, carbon black as a conductive agent, and polyvinylidene fluoride as a binder are mixed in N-methylpyrrolidone solvent to make the weight ratio of positive electrode active material: conductive agent: binder 98.5:0.5:1, so as to prepare a second positive electrode slurry.
[0117] After coating a first positive electrode slurry composition onto an aluminum current collector and drying it to form a first positive electrode active material layer, a second positive electrode slurry composition is coated onto the first positive electrode active material layer, dried at 130°C, and then rolled to prepare the positive electrode. In this case, based on the cross-section of the positive electrode, the thickness of the first positive electrode active material layer is 98 μm, the thickness of the second positive electrode active material layer is 2 μm, and the positive electrode loading is 7 mAh / cm³. 2 .
[0118] Comparative Example 1
[0119] LiNi with a cation mixing degree of 1.5% was used as the positive electrode active material. 0.9 Co 0.04 Mn 0.06 O2, carbon black as a conductive agent, and polyvinylidene fluoride as a binder are mixed in N-methylpyrrolidone solvent to make the weight ratio of positive electrode active material: conductive agent: binder 98.5:0.5:1, so as to prepare positive electrode slurry.
[0120] The positive electrode slurry composition was coated onto an aluminum current collector, dried at 130°C, and then rolled to prepare the positive electrode. In this case, the thickness of the positive electrode active material layer was 100 μm, and the positive electrode loading was 6.9 mAh / cm³. 2 .
[0121] Comparative Example 2
[0122] LiNi with a cation mixing degree of 1.4% was used as the positive electrode active material. 0.92 Co 0.04 Mn 0.04 O2, carbon black as a conductive agent, and polyvinylidene fluoride as a binder are mixed in N-methylpyrrolidone solvent to make the weight ratio of positive electrode active material: conductive agent: binder 98.5:0.5:1, so as to prepare positive electrode slurry.
[0123] The positive electrode slurry composition was coated onto an aluminum current collector, dried at 130°C, and then rolled to prepare the positive electrode. In this case, the thickness of the positive electrode active material layer was 100 μm, and the positive electrode loading was 7 mAh / cm³. 2 .
[0124] Comparative Example 3
[0125] LiNi with a cation mixing degree of 1.5% was used as the positive electrode active material. 0.94 Co 0.04 Mn 0.02 O2, carbon black as a conductive agent, and polyvinylidene fluoride as a binder are mixed in N-methylpyrrolidone solvent to make the weight ratio of positive electrode active material: conductive agent: binder 98.5:0.5:1, so as to prepare positive electrode slurry.
[0126] The positive electrode slurry composition was coated onto an aluminum current collector, dried at 130°C, and then rolled to prepare the positive electrode. In this case, the thickness of the positive electrode active material layer was 100 μm, and the positive electrode loading was 7 mAh / cm³. 2 .
[0127] Comparative Example 4
[0128] LiNi with a cation mixing degree of 1.5% was used as the first positive electrode active material. 0.9 Co 0.04 Mn 0.06 O2, carbon black as a conductive agent, and polyvinylidene fluoride as a binder are mixed in N-methylpyrrolidone solvent to make the weight ratio of positive electrode active material: conductive agent: binder 98.5:0.5:1, so as to prepare the first positive electrode slurry.
[0129] LiNi with a cation mixing degree of 1.3% was used as the second positive electrode active material. 0.9 Co0.05 Mn 0.05 O2, carbon black as a conductive agent, and polyvinylidene fluoride as a binder are mixed in N-methylpyrrolidone solvent to make the weight ratio of positive electrode active material: conductive agent: binder 98.5:0.5:1, so as to prepare a second positive electrode slurry.
[0130] After coating a first positive electrode slurry composition onto an aluminum current collector and drying it to form a first positive electrode active material layer, a second positive electrode slurry composition is coated onto the first positive electrode active material layer, dried at 130°C, and then rolled to prepare the positive electrode. In this case, based on the cross-section of the positive electrode, the thickness of the first positive electrode active material layer is 98 μm, the thickness of the second positive electrode active material layer is 2 μm, and the positive electrode loading is 6.9 mAh / cm³. 2 .
[0131] Comparative Example 5
[0132] LiNi with a cation mixing degree of 1.2% was used as the first positive electrode active material. 0.88 Co 0.05 Mn 0.07 O2, carbon black as a conductive agent, and polyvinylidene fluoride as a binder are mixed in N-methylpyrrolidone solvent to make the weight ratio of positive electrode active material: conductive agent: binder 98.5:0.5:1, so as to prepare the first positive electrode slurry.
[0133] LiNi, with a cation mixing degree of less than 1%, will be used as the second positive electrode active material. 0.85 Co 0.07 Mn 0.08 O2, carbon black as a conductive agent, and polyvinylidene fluoride as a binder are mixed in N-methylpyrrolidone solvent to make the weight ratio of positive electrode active material: conductive agent: binder 98.5:0.5:1, so as to prepare a second positive electrode slurry.
[0134] After coating a first positive electrode slurry composition onto an aluminum current collector and drying it to form a first positive electrode active material layer, a second positive electrode slurry composition is coated onto the first positive electrode active material layer, dried at 130°C, and then rolled to prepare the positive electrode. In this case, based on the cross-section of the positive electrode, the thickness of the first positive electrode active material layer is 98 μm, the thickness of the second positive electrode active material layer is 2 μm, and the positive electrode loading is 6.9 mAh / cm³. 2 .
[0135] Comparative Example 6
[0136] LiNi, with a cation mixing degree of less than 1%, will be used as the first positive electrode active material. 0.85 Co 0.07 Mn 0.08O2, carbon black as a conductive agent, and polyvinylidene fluoride as a binder are mixed in N-methylpyrrolidone solvent to make the weight ratio of positive electrode active material: conductive agent: binder 98.5:0.5:1, so as to prepare the first positive electrode slurry.
[0137] LiNi with a cation mixing degree of 1.5% was used as the second positive electrode active material. 0.9 Co 0.04 Mn 0.06 O2, carbon black as a conductive agent, and polyvinylidene fluoride as a binder are mixed in N-methylpyrrolidone solvent to make the weight ratio of positive electrode active material: conductive agent: binder 98.5:0.5:1, so as to prepare a second positive electrode slurry.
[0138] After coating a first positive electrode slurry composition onto an aluminum current collector and drying it to form a first positive electrode active material layer, a second positive electrode slurry composition is coated onto the first positive electrode active material layer, dried at 130°C, and then rolled to prepare the positive electrode. In this case, based on the cross-section of the positive electrode, the thickness of the first positive electrode active material layer is 98 μm, the thickness of the second positive electrode active material layer is 2 μm, and the positive electrode loading is 6.8 mAh / cm³. 2 .
[0139] Experimental Example 1
[0140] After preparing electrode assemblies by setting porous polyethylene membranes between the positive electrodes and lithium metal negative electrodes prepared in Examples 1 to 9 and Comparative Examples 1 to 6, an electrolyte was injected to prepare a lithium secondary battery. The electrolyte contained 2% by weight of vinylene carbonate (VC) and 1M LIPF6 was dissolved in an organic solvent in which ethylene carbonate (EC): dimethyl carbonate (DMC): ethyl methyl carbonate (EMC) were mixed in a ratio of 3:4:3.
[0141] Each lithium secondary battery prepared as described above was charged to 4.25V at a constant current of 0.1C at 25°C, and then discharged to 2.5V at a constant current of 0.1C to measure the discharge capacity.
[0142] The measurement results are shown in Table 1 below.
[0143] Experiment Example 2
[0144] The process of charging each lithium secondary battery prepared in Experimental Example 1 to 4.25V at 45°C with a constant current of 0.3C and discharging each lithium secondary battery to 2.5V with a constant current of 0.3C is defined as one cycle. After 100 charge-discharge cycles, the capacity retention rate after 100 cycles is measured to measure the lifetime characteristics.
[0145] The measurement results are shown in Table 1 below.
[0146] [Table 1]
[0147]
[0148] As shown in Table 1, the lifespan characteristics of lithium secondary batteries using the cathodes of Examples 1 to 9 (wherein the Ni / Co ratio of the first and second cathode active materials satisfies the scope of the present invention) are significantly improved compared to lithium secondary batteries using the cathodes of Comparative Examples 1 to 6.
Claims
1. A positive electrode comprising a positive electrode current collector, a first positive electrode active material layer formed on the positive electrode current collector and comprising a first positive electrode active material, and a second positive electrode active material layer formed on the first positive electrode active material layer and comprising a second positive electrode active material. in, The first positive electrode active material comprises a lithium nickel cobalt oxide, wherein the nickel content in all metal components other than lithium is 80 atm% or more, and the second positive electrode active material comprises a lithium nickel cobalt oxide, wherein the nickel content in all metal components other than lithium is 80 atm% or more. The first positive electrode active material comprises a first lithium nickel cobalt oxide represented by Formula 1: [Formula 1] Li a1 [Ni x1 Co y1 M 1 z1 M 2 w1 ]O2 In Equation 1, M 1 It is Mn, Al, or a combination thereof. M 2 It is selected from at least one of the group consisting of Zr, B, W, Mg, Ce, Hf, Ta, La, Ti, Sr, Ba, F, P, and S, and 0.8≤a1≤1.2, 0.90≤x1<1, 0 <y1<0.10,0<z1<0.10,0≤w1<0.10,18≤x1 / y1; The second positive electrode active material comprises a second lithium nickel cobalt oxide represented by Formula 2: [Equation 2] Li a2 [Ni x2 Co y2 M 3 z2 M 4 w2 ]O2 In Equation 2, M 3 It is Mn, Al, or a combination thereof. M 4 It is selected from at least one of the group consisting of Zr, B, W, Mg, Ce, Hf, Ta, La, Ti, Sr, Ba, F, P, and S, and 0.8≤a²≤1.2, 0.80≤x²<0.90, 0 <y2<0.20,0<z2<0.20,0≤w2<0.20,x2 / y2<18; The nickel / cobalt molar ratio of the first positive electrode active material is 18 or higher, and The nickel / cobalt molar ratio of the second positive electrode active material is less than 18.
2. The positive electrode as described in claim 1, wherein, The nickel / cobalt molar ratio of the first positive electrode active material is 18 to 50, and The nickel / cobalt molar ratio of the second positive electrode active material is 5 to 17.
8.
3. The positive electrode as described in claim 1, wherein, The cation mixing degree of the first positive electrode active material is greater than 1.2%, and The cation mixing degree of the second positive electrode active material is less than 1.2%.
4. The positive electrode as described in claim 3, wherein, The cation mixing degree of the first positive electrode active material is greater than 1.2% and less than 2%, and The cation mixing degree of the second positive electrode active material is less than 1.0%.
5. The positive electrode as described in claim 1, wherein, The nickel content in all metal components other than lithium in the first positive electrode active material is 90 mol% or more, and The nickel content in all metal components other than lithium in the second positive electrode active material is more than 80 mol% and less than 90 mol%.
6. The positive electrode as described in claim 1, wherein, The thickness of the second positive electrode active material layer is less than 10 μm.
7. The positive electrode as described in claim 1, wherein, The positive electrode has a loading capacity of 4 mAh / cm³. 2 above.
8. The positive electrode as described in claim 7, wherein, The positive electrode has a loading capacity of 4 mAh / cm³. 2 Up to 20mAh / cm 2 .
9. A lithium secondary battery comprising a positive electrode according to any one of claims 1 to 8.
Citation Information
Patent Citations
Method and device for predicting disease using segmentating vessel in eye image
KR1020210026597A
Secondary battery having improved high-temperature properties
US20200395603A1
KR20190012839A